Do couvert ao café: pescadores, memórias e comidas - Stefanutti, Paola (2015)
This academic meal shows the research about fishermen's memories from Foz do Iguaçu. Analyses were performed from accounts of experiences, everyday and feeding. From the Couvert to the Coffee: fishermen, memories and food it follows the sequence of a meal, addressing the following items: the Cover charge introduces the reader to the text bringing the objectives and characteristics of the research object. At the Entree" is present the theoretic and methodological approach of the research, showing the fishermen, the methods, the interviews and their scenarios. Continuing, the Fish section brings a discussion of being fisherman and an analysis of the accounts of fishermen experiences approaching its limits, physical and human-symbolic, the fisherman yesterday and the fisherman today, the fisherman and the children and reports on smuggling. In the next section, the Main Course has fishermen reports and their families about food memories and their discussions and developments. At Dessert , there is a moment of reflection and pause of the meal forward to ingested foods. Containing ruminates about the food and the aliment, the food groups and the fishermen, the symbolic representation of the beef in the diet of the fishermen, the food as identity and as limit and ends with a more open discussion of eating behaviors. And like a good meal ends with the trivial and digestive Coffee . This conclusion has the taste of the wanting more, with the epilogue or the preface stories and fishermen memories from their exciting accounts, ending with reflections of the academic path. The methodological procedure adopted in this paper seeks to interpret data obtained through the accounts and is considered a thematic oral research. Nine interviews and ten conversations with people involved in fishery were carried out. The looks to these sources, these characters in the history of Foz do Iguaçu, make this thesis be memories and source. This writing goes to the general reader and the scholar. There is something to add to both, each in its particularity. So from that perspective, it can be said that this study is dedicated to the everyday practices of the fishermen under the fishing range, border, family and food. This writing is a meal to ruminate intellectually. Throughout the survey foundations that contributed to a transdisciplinary understanding of the food aspect are created, highlighting feeding as one of the tools of the social sciences. It is also expected to contribute to the record of memories and to the history of food in town.